2015
DOI: 10.1152/ajpendo.00245.2015
|View full text |Cite
|
Sign up to set email alerts
|

Physiology in Medicine: update on lifestyle determinants of postprandial triacylglycerolemia with emphasis on the Mediterranean lifestyle

Abstract: Maraki MI, Sidossis LS. Update on lifestyle determinants of postprandial triacylglycerolemia with emphasis on the Mediterranean lifestyle. Am J Physiol Endocrinol Metab 309: E440 -E449, 2015. First published July 7, 2015; doi:10.1152/ajpendo.00245.2015.-This review updates the effect of lifestyle on plasma triacylglycerols (TAG) in the postprandial state, commonly reported as postprandial lipemia (PPL), an independent risk factor for cardiovascular diseases (CVD). Numerous studies have shown that Mediterranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
0
3
0
1
Order By: Relevance
“…However, the epigenomic mechanisms involved in these processes are not thoroughly known. Epidemiological studies have revealed how favorable dietary patterns, such as the Mediterranean diet during pregnancy and early childhood can have a protective effect, with reduced risk of obesity, diabetes, cardiovascular risk factor, some cancers and NAFLD [93][94][95][96][97]. Particularly, these beneficial effects reflect composite dietary patterns, and are difficult to attribute to a single dietary element.…”
Section: Polyunsaturated Fatty Acids (Pufas) and Epigeneticsmentioning
confidence: 99%
“…However, the epigenomic mechanisms involved in these processes are not thoroughly known. Epidemiological studies have revealed how favorable dietary patterns, such as the Mediterranean diet during pregnancy and early childhood can have a protective effect, with reduced risk of obesity, diabetes, cardiovascular risk factor, some cancers and NAFLD [93][94][95][96][97]. Particularly, these beneficial effects reflect composite dietary patterns, and are difficult to attribute to a single dietary element.…”
Section: Polyunsaturated Fatty Acids (Pufas) and Epigeneticsmentioning
confidence: 99%
“…Nevertheless, among Mediterranean populations for whom olive oil is an integral part of their diets, compliance to such fat-limited diets might be poor. In fact, a growing body of evidence indicates that adherence to the Mediterranean diet (MedDiet) is associated with improved glucoregulation, blood lipid levels and overall metabolic profile, presumably due to the types of fat sources it includes, these being predominantly monounsaturated fatty acids (MUFAs) and limited amounts of saturated fatty acids (SFAs) [12,13]. However, the MedDiet per se does not lead to substantial weight loss, unless it is energy-restricted [14,15] or modified [16].…”
Section: Of 15mentioning
confidence: 99%
“…Although postprandial lipemia is a physiological and transient mechanism for acquisition of fatty acids and other nutrients from the diet, it can become pathological, notably when the circulating TG concentrations are exacerbated or when the circulating TG clearance time is too long. 14,15 The most common alterations associated with the postprandial metabolism of dietary fats are oxidative stress and inflammation. 13 However, the potential effects of postprandial TRLs on damage to RPE cells have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%